NSAID-sparing effect of glucosamine hydrochloride in patients with knee osteoarthritis: an analysis of data from a French database. (February 2014) - Bertin, Philippe; Taieb, Charles
Abstract Objective: Knee osteoarthritis (OA) is a major cause of pain, functional limitation, and reduced quality-of-life, particularly in older adults. This study evaluated the 'real world' NSAID-sparing effect of glucosamine (specifically Structoflex®) in patients with knee OA compared with a control population of patients who did not receive a slow-acting symptomatic anti-osteoarthritis agent. Research design and methods: This analysis was conducted over a 1-year follow-up period. Data were sourced from the French Disease Analyzer (IMS Lifelink EMR™) database. Main outcome measures: The primary measure was the NSAID-sparing effect produced by Structoflex® compared with a matched control group. Secondary measures included an evaluation of the change in the number of general practitioner visits and use of other medicinal products related to knee OA. Results: A total of 11, 772 patients (67.66% female) were included in the analysis (436 and 11, 336 patients in the Structoflex® and control groups, respectively). Most patients were aged 50–65 years (58.72%); 19.5% of patients were aged >76 years. At study inclusion, 51.61% of patients had experienced OA for <1 year. Prior to starting Structoflex®, 51.61% of patients had received an NSAID prescription. Significantly more patients who were receiving an NSAID at the time of starting Structoflex® discontinued their NSAID treatment during the follow-up period compared with patients in the control group (32% vs 23%; p = 0.0452). During the 1-year follow-up period, the total mean duration of NSAID prescription (30.39 ± 38.64 days vs 37.82 ± 54.62 days; p = 0.0109) and the mean number of days (calculated using Defined Daily Dose) on NSAID (45.12 ± 49.03 days vs 53.00 ± 71.14 days; p = 0.0333) was significantly lower in Structoflex®-treated patients compared with control group patients. Conclusions: This large 'real world' analysis demonstrated a significant NSAID-sparing effect of glucosamine in patients with knee OA.